Revitalisasi Fasilitas Belajar Anak Usia Dini dalam Mendukung Tujuan SDG's Sektor Pendidikan di Pendidikan Anak Usia Dini - Suwandi Suwandi; Nurul Imani Kurniawati; Riandhita Eri Werdani; Kholidin (Yayasan Sumber Daya Manusia Cerdas, 2023)
One focus of the SDGs is children. It is important to pay special attention and ensure that children have equal access to education and health. One of the efforts that can be made to realize equality in the field of education is to provide proper educational facilities for children. This service activity aims to provide facilities that support the learning process of children in Seroja PAUD. Implementation of activities begins with initial observations, inventory of needs, determination of priority scale and finally the implementation of activities. The output of this activity is the availability of learning facilities and infrastructure for children at Seroja PAUD.